Effects of alfalfa saponins on the production performance, serum biochemical factors, and immune factors in Small-Tailed Han sheep - Yang, Fan; Yang, Fang; Zhai, Zhen-Han; Wang, Sai-Qiao; Zhao, Lu; Zhang, Bing-Lei; Chen, Jun-Cheng; Wang, Yu-Qin (Frontiers in Veterinary Science, 2022)
This study aimed to determine the potential effects of alfalfa saponins on the production performance, serum biochemical factors, and immune factors in sheep. Twenty Small-Tailed Han sheep were equally and randomly divided into Groups 1–4, fed with diets containing 0, 5, 10, and 20 g alfalfa saponins per kg, respectively, for 40 consecutive days. During the treatments, the body weight change was recorded for each sheep. Before, during, and after the treatments of alfalfa saponins, serum was collected from each group to compare the levels of biochemical and immune factors. All sheep were killed after the treatments, and the longissimus dorsi muscle was collected to compare the meat quality. The results validated the effects of alfalfa saponins on the growth performance and meat quality in Small-Tailed Han sheep, and the supplementation level of 10 g/kg was the best. Alfalfa saponins also had effects on the levels of biochemical factors in serum. However, both dose- and time-dependent effects were observed. After a shorter feeding period (14 days), the concentrations of cholesterol (CHOL) and low-density lipoprotein (LDL) in Groups 2, 3, and 4 were all lower than those in the control group; however, when alfalfa saponins were continuously fed, this effect was not apparent or even gone. Supplying alfalfa saponins increased serum concentrations of IgA, IgG, IgE, IgM, IL-1, IFN-α, and IFN-β. And this effect was distinctly observed in Groups 3 and 4. Based on the current results, the alfalfa saponins concentration of 10 g/kg (for 14 consecutive days) could be suggested as the optimum ratio for good health conditions of Small-Tailed Han sheep.